NEED ANALYSIS FOR DEVELOPING PARAGRAPH WRITING MATERIALS BASED ON PROBLEM-BASED LEARNING MODEL FOR INDONESIAN EFL LEARNERS - Ilham, Ilham (English Review: Journal of English Education, 2023)
This study aims to explore models of Paragraph Writing materials based on problem-based learning needed by students and lecturers. A descriptive qualitative method design is employed. It involves thirty- three students and two instructors of the English Department of a private university in Mataram West Lombok, Indonesia who attend paragraph writing class in the academic year 2023-2024. To collect the data, questionnaires, and interviews were used. The finding revealed that students and lecturers preferred teaching materials with understanding part of the paragraph, unity and coherence, and paragraph organization. The topic of paragraph writing material on vocabulary, subject-verb agreement, and part of speech. Learning exercises provide in individual and group, learning exercises which focus on writing topic sentences, supporting sentences and concluding sentences.  Evaluation from both theoretical and practical elements, to understand the concept of problem-based learning. To conclude, designing a model of teaching materials for paragraph writing materials based on problem-based learning is needed to conduct to keep up with updated insightful needs. By giving information on the needs of students and educators, this study has shown the capacity to bridge the gap and also recommendation to conduct need analysis regularly for designing Paragraph Writing Material. Keywords: Paragraph writing material, problem-based learning, EFL learners